From Human-like Brands to Positive Consumer Attitudes: Applying Self-Congruence Theory to Brand Anthropomorphism and Personality - Widyaningrum, Firda Amalia; Suwandari, Lusi (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
This study examines how brand anthropomorphism influences consumers’ positive attitudes toward brands, directly and through the mediating role of brand personality, based on the self-congruence theory. Using a quantitative survey method, data were collected from 231 respondents familiar with brands employing anthropomorphic strategies, such as Wizz Mie, Roti’O, Hokben, and Starbucks. Respondents had purchased from the brands more than three times and followed their social media accounts. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that anthropomorphism significantly influences brand personality, and both directly and indirectly enhances consumers’ positive attitudes. Brand personality plays a partial mediating role, showing that consumers evaluate brands more positively when they perceive human-like traits that align with their self-concept. These insights highlight the importance of incorporating anthropomorphic elements in brand communication to strengthen emotional connections and improve brand perception.